Genetic Diversity of Selected Mangifera Species Revealed by Inter Simple Sequence Repeats Markers. (3rd November 2015) - Ariffin, Zulhairil; Md Sah, Muhammad Shafie; Idris, Salma; Hashim, Nuradni
Abstract : ISSR markers were employed to reveal genetic diversity and genetic relatedness among 28 Mangifera accessions collected from Yan (Kedah), Bukit Gantang (Perak), Sibuti (Sarawak), and Papar (Sabah). A total of 198 markers were generated using nine anchored primers and one nonanchored primer. Genetic variation among the 28 accessions of Mangifera species including wild relatives, landraces, and clonal varieties is high, with an average degree of polymorphism of 98% and mean Shannon index, H 0 = 7.50 . Analysis on 18 Mangifera indica accessions also showed high degree of polymorphism of 99% and mean Shannon index, H 0 = 5.74 . Dice index of genetic similarity ranged from 0.0938 to 0.8046 among the Mangifera species. The dendrogram showed that the Mangifera species were grouped into three main divergent clusters. Cluster 1 comprised 14 accessions from Kedah and Perak. Cluster II and cluster III comprised 14 accessions from Sarawak and Sabah. Meanwhile, the Dice index of genetic similarity for 18 accessions of Mangifera indica ranged from 0.2588 to 0.7742. The dendrogram also showed the 18 accessions of Mangifera indica were grouped into three main clusters. Cluster I comprised 10 landraces of Mangifera indica from Kedah. Cluster II comprised 7 landraces of Mangifera indica followed by Chokanan to form Cluster III.